2013
DOI: 10.1002/ijop.12014
|View full text |Cite
|
Sign up to set email alerts
|

What my parents make me believe in learning: The role of filial piety in Hong Kong students' motivation and academic achievement

Abstract: Chinese students are well-known for their academic excellence. However, studies that explore the underlying mechanism of how cultural factors relate to the motivational process and academic achievement of Chinese students have been limited. This study aimed to examine the role of filial piety in shaping Chinese students' theories of intelligence so as to obtain a clearer understanding of the process by which parent-child connectedness is linked to Chinese students' academic achievement. A sample of 312 univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 18 publications
(35 reference statements)
4
36
0
Order By: Relevance
“…Second, the participants found ways to justify the authoritative parenting they received through their desire and actualization of closely bonding with the parents. This explains how the students were able to reconcile the "double-edged sword" (Pan et al, 2013) of collectivist culture (see also Chen & Wong, 2014;Chow & Chu, 2007). Particularly if the parents were autonomy-supportive, filial piety flourished since children believed that their parents wanted them to pursue their dreams.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Second, the participants found ways to justify the authoritative parenting they received through their desire and actualization of closely bonding with the parents. This explains how the students were able to reconcile the "double-edged sword" (Pan et al, 2013) of collectivist culture (see also Chen & Wong, 2014;Chow & Chu, 2007). Particularly if the parents were autonomy-supportive, filial piety flourished since children believed that their parents wanted them to pursue their dreams.…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, Fuligni and Zhang (2004) identified that obligation to family by bringing honor and repaying parents for their upbringing, respecting parental authority, and being willing to sacrifice for the family was associated with higher levels of academic motivation among adolescents. Furthermore, Chen and Wong (2014) found that filial piety beliefs affect an adolescent's understanding of academic intelligence and achievement.…”
Section: Filial Piety In Confucian Heritage Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, AFP has been found to exert different effects on different variables. In addition, a study by W.-W. Chen and Wong (2014) found that AFP had a negative indirect effect on the academic results of Hong Kong university students. However, Jin (2009) reported that C-AFP did not have a significant influence on career decision self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jin (2009) reported that C-AFP did not have a significant influence on career decision self-efficacy. In addition, a study by W.-W. Chen and Wong (2014) found that AFP had a negative indirect effect on the academic results of Hong Kong university students. The differentiated impact of AFP may help explain the difference between our findings and those of Li's study with Shanghai university students.…”
Section: Discussionmentioning
confidence: 99%